The Effect Of Providing Information On Implant Installation Procedures To The Anxiety Level Of The Implant Acceptor Candidate In Gorontalo City - PUSPITA SUKMAWATY RASYID (Jurnal Nasional Ilmu Kesehatan, 2019)
Fear of pain during insertion of Impant is a major source of anxiety for many women, even though the actual pain experienced is not as severe as imagined. Providing information on Implant installation procedure is one of the ways that can be done to reduce the level of anxiety.This study aims to analyze the effect of providing information on Implant installation procedure to the anxiety level of the Implant acceptor candidate in Gorontalo City.This type of research is Experimental Research with pretest posttest design. The number of respondents was 30 people, which were observed by the level of anxiety before and after being given information on Implant installation procedure. This study uses the Consecutive Sampling method. The independent variable is the providing information on Implant installation procedure and the dependent variable is the anxiety level of the Implant acceptor candidate.The results of the study based on paired sample T-test analysis with significance levels α = 0.05 were obtained by the effect of providing information on Implant installation procedure to the anxiety level of Implant acceptor candidates in Gorontalo City with the acquisition of the p value is 0,000 with α = 0, 05.Conclusion; There is the Effect of Providing Information on Implant Installation Procedures to the Anxiety Level of Implant Acceptor Candidates in Gorontalo City. Keywords: Information on Installation, Anxiety, Implant Contraception